2013
DOI: 10.1016/j.nuclphysa.2012.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Hypernuclear matter in strong magnetic field

Abstract: Compact stars with strong magnetic fields (magnetars) have been observationally determined to have surface magnetic fields of order of 10 14 − 10 15 G, the implied internal field strength being several orders larger. We study the equation of state and composition of dense hypernuclear matter in strong magnetic fields in a range expected in the interiors of magnetars. Within the non-linear Boguta-Bodmer-Walecka model we find that the magnetic field has sizable influence on the properties of matter for central m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 78 publications
(111 reference statements)
4
74
0
Order By: Relevance
“…Comparing our work with [36] we show that significant differences on maximum masses and their respective radii for stronger magnetic fields can be obtained depending on the choice of the parameters for slow and fast decays of the density dependent magnetic field. This means that different combinations of parameters can generate controllable values for masses and radii, as expected from the results obtained in [30].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Comparing our work with [36] we show that significant differences on maximum masses and their respective radii for stronger magnetic fields can be obtained depending on the choice of the parameters for slow and fast decays of the density dependent magnetic field. This means that different combinations of parameters can generate controllable values for masses and radii, as expected from the results obtained in [30].…”
Section: Introductionsupporting
confidence: 61%
“…In [30], different profiles for the density dependence of the magnetic field were studied in the context of hadronic stars and the authors concluded that the equation of state is insensitive to magnetic fields lower than 10 18 G, a behaviour already observed in [36,38,39] for different models. Moreover, they found that for magnetic fields higher than 10 18 G, matter becomes unstable due to the increase of anisotropic effects on the pressure.…”
Section: Resultsmentioning
confidence: 94%
“…Over the years, it has been shown that the presence of strong magnetic fields significantly affects the energy levels of charged particles due to Landau quantization. These effects have been taken into account in the EoS of models in order to describe hyperon stars (Chakrabarty et al 1997;Broderick et al 2000Broderick et al , 2002Lopes & Menezes 2012;Sinha et al 2013;Casali et al 2014;Gomes et al 2014;Gao et al 2015), quark stars (Perez Martinez et al 2008;Felipe et al 2011;Orsaria et al 2011;Paulucci et al 2011;Denke & Pinto 2013;Dexheimer et al 2014;Isayev 2015), hybrid stars (Rabhi et al 2009;Dexheimer et al 2012Dexheimer et al , 2013, and stars with meson condensates Schramm et al (2015). The effects of the anomalous magnetic moment (AMM) were also investigated through the corresponding coupling of the baryons to the electromagnetic field tensor (see Canuto & Chiu 1968a;Broderick et al 2000Broderick et al , 2002Strickland et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, below the field values 10 18 G the abundances of baryons for non-zero B are indistinguishable from those in the B = 0 case (see Ref. [7] and references therein).…”
Section: Microphysical Inputmentioning
confidence: 98%